2018
DOI: 10.5194/hess-22-2971-2018
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater withdrawal in randomly heterogeneous coastal aquifers

Abstract: Abstract. We analyze the combined effects of aquifer heterogeneity and pumping operations on seawater intrusion (SWI), a phenomenon which is threatening coastal aquifers worldwide. Our investigation is set within a probabilistic framework and relies on a numerical Monte Carlo approach targeting transient variable-density flow and solute transport in a three-dimensional randomly heterogeneous porous domain. The geological setting is patterned after the Argentona river basin, in the Maresme region of Catalonia (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Li et al (2016) reported a similar influence of heterogeneity on the mixing zone for a domain of 130 × 6 m and found that heterogeneity significantly affects SGD patterns. Siena and Riva (2018) assessed the role of heterogeneity under pumping operations. Their simulation results suggested that aquifer heterogeneity increases the area of the mixing zone and slows the intrusion process.…”
mentioning
confidence: 99%
“…Li et al (2016) reported a similar influence of heterogeneity on the mixing zone for a domain of 130 × 6 m and found that heterogeneity significantly affects SGD patterns. Siena and Riva (2018) assessed the role of heterogeneity under pumping operations. Their simulation results suggested that aquifer heterogeneity increases the area of the mixing zone and slows the intrusion process.…”
mentioning
confidence: 99%
“…Bear et al (2001) performed a 3-D numerical simulation of the heterogeneous coastal aquifer in Israel. Held et al (2005) investigated the effect of 2-D heterogeneity in the Henry Problem and found using numerical simulations that heterogeneity results in a reduction in the extent of SWI and widening of the mixing zone, a phenomenon also observed in previous studies (e.g., Kerrou & Renard, 2009;Siena & Riva, 2018). Held et al (2005) also proposed geometric mean as the effective permeability for the isotropic case, the same as that in the single-density flow, however, valid only in the case of small-scale heterogeneities.…”
Section: Introductionmentioning
confidence: 60%
“…The conceptual model of a sharp interface is still frequently applied, although it does not account for mixing along the interface and therefore simplifies the problem (e.g. Mehdizadeh et al 2017;Siena and Riva 2018). Whereas a sharp interface approximation can be applied under certain conditions (cf.…”
Section: Processes Related To Saltwater Intrusionmentioning
confidence: 99%
“…Therefore, the validity of a sharp interface applied on real case scenarios is already limited in unconsolidated material (e.g. Reilly and Goodman 1985;Pool and Carrera 2011;Llopis-Albert and Pulido-Velazquez 2014;Siena and Riva 2018). Nevertheless, the application of the sharp interface approximation for sustainable water-resources management is a conservative measure, since it overestimates the frontal extent of the SWI and underestimates critical pumping rates (Pool and Carrera 2011).…”
Section: Processes Related To Saltwater Intrusionmentioning
confidence: 99%